PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PADA INDUSTRI KERAJINAN KULIT "KARYA PAHALA GROUP" DI MAGETAN - Henrika Arliani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
This result  aims to determine  employee  incentive  marketing  in Leather  Craft Industry  "Karya  Pahala  Group"  in Magetan,  to determine  employee  performance   mar- keting  industry Leather  Craft "Karya  Pahala  Group"  in Magetan  and to investigate  the influence of incentives on employee performance  marketing  industry Leather Craft "Karya Pahala  Group"  in Magetan.  Determination   of the sample in this study using a sample that is saturated  all the existing  employees   in the leather  industry  "Karya  Pahala  Group"  in Magetan   totaling  45 employees.   Data  colJection  using  questionnaires   and documenta- tion. In the statistical  methods  used to analyze  data product  moment correlation  with the independent  variables  and variable  incentives  tied to performance.   To test the validity  of the research  hypothesis  regression  test was used to analyze  the data using SPSS for Win- dows  16.0. The results showed  that incentives have a positive effect as well as the perfor- mance  of employees  in the leather  industry  "Karya  Pahala  Group"  in Magetan.  It is de- rived from the value of the F test, the value of39.583   while Fcount  Ftable value of 4.067. On the other hand Sighit known  value of 0.000 and a value of 0.05 Sigprob.  This means that  Fcount  > Ftable  (> 4.067  39.583)  < Sighit  Sigprob  (0.000  Sigprob  < 0.05).  This means that in case of refusal H, which indicates  that there is influence  between employee performance   incentives  on leather  industry  "Karya  Pahala  Group"  in Magetan.  Besides the regression  coefficient  obtained  (t test) with  a value of 6.291  while  the value  tcount ttable of 1.681. On the other hand Sighit value of 0.000 and a value of 0.05 Sigprob. This means tcount>  ttable (6.291 > 1.681) or<  Sighit Sigprob (0.000 < 0.05). This means that in case of refusal H, indicating that incentives have a different influence on employee performance. In addition the results obtained from testing the validity of the value of r 'Y > 0.295 rtabel. This means that all the questions in the questionnaire incentive is valid. Besides reliability test results obtained from the value of Cronbach's Alpha of 0.785 and 0.760> 0.6. This means that the data collected reliable (trustworthy).